Study on Evolution Characteristics of Regenerated Roof Structure in Downward Mining of Bifurcated Coal Seam. (31st August 2021) - Hu, Ru; Wu, Jiwen; Shi, WenBao; Zhai, Xiaorong; Huang, Kai
Abstract : In recent years, the structural evolution characteristics of the regenerated roof of the lower coal seam have become a research hotspot when the bifurcation coal seam is mined downward. In this paper, taking the bifurcation coal seam of Xutuan Coal Mine in China as an example, the structural evolution characteristics of regenerated roof under the influence of mining in bifurcation coal seam are comprehensively studied by theoretical analysis, field measurement, and indoor similar simulation experiment. The stress transfer law in the floor after mining in the upper coal seam is also analyzed. The results show the overburden structure and stress field change caused by upper coal seam mining. The caving and fracture zones are formed in the roof, the average height of the caving zone is 8.28 m, and the one of the fracture zone is 34.91 m. The results of the field test verify the accuracy of theoretical analysis and similar simulation test results. According to the relative size of the depth of the strong failure zone of the coal seam floor and the coal seam spacing, the rock mass structure of the regenerated roof of lower coal seam is divided into three types: fractured rock mass + scattered rock mass (I), fractured rock mass + scattered rock mass + fractured rock mass (II), and fractured rock mass + bulk rock mass + fractured rock mass + layered rock mass (III), and the stability of the three types of regenerated roof structure is evaluated: III > II > I. The research in this paper can provide a theoretical basis for determining the target area of broken roof control under the mining conditions of bifurcation coal seam and provide guidance for the selection of the location and parameters of the grouting borehole for roof reinforcement.